2012
DOI: 10.1105/tpc.112.100230
|View full text |Cite
|
Sign up to set email alerts
|

The Grapevine Expression Atlas Reveals a Deep Transcriptome Shift Driving the Entire Plant into a Maturation Program  

Abstract: We developed a genome-wide transcriptomic atlas of grapevine (Vitis vinifera) based on 54 samples representing green and woody tissues and organs at different developmental stages as well as specialized tissues such as pollen and senescent leaves. Together, these samples expressed ;91% of the predicted grapevine genes. Pollen and senescent leaves had unique transcriptomes reflecting their specialized functions and physiological status. However, microarray and RNA-seq analysis grouped all the other samples into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
417
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(445 citation statements)
references
References 63 publications
28
417
0
Order By: Relevance
“…To this end, a collection of multitissue transcriptome data sets was identified from several species, each possessing an association with suberin deposition. In addition to (1) apple (i.e., russet clone) and (2) tomato (i.e., SlDCR-RNAi) fruit transcriptome data sets described above, this collection included gene expression data sets of (3) seed tissues during development in Arabidopsis (Le et al, 2010), (4) all major organs of grapevine (Vitis vinifera) (Fasoli et al, 2012), (5) multiple organs of tomato (Tomato Gene Consortium, 2012), (6) potato (Xu et al, 2011), and (7) the roots (A) Two Golden Delicious apple clones were analyzed: the normal skinned 'Reinders' clone and the russeted 'Rugiada' clone. 'Rugiada' displays a rough, brown, and cracked fruit surface.…”
Section: Comparative Transcriptome Analysis Reveals a Multispecies Gementioning
confidence: 99%
“…To this end, a collection of multitissue transcriptome data sets was identified from several species, each possessing an association with suberin deposition. In addition to (1) apple (i.e., russet clone) and (2) tomato (i.e., SlDCR-RNAi) fruit transcriptome data sets described above, this collection included gene expression data sets of (3) seed tissues during development in Arabidopsis (Le et al, 2010), (4) all major organs of grapevine (Vitis vinifera) (Fasoli et al, 2012), (5) multiple organs of tomato (Tomato Gene Consortium, 2012), (6) potato (Xu et al, 2011), and (7) the roots (A) Two Golden Delicious apple clones were analyzed: the normal skinned 'Reinders' clone and the russeted 'Rugiada' clone. 'Rugiada' displays a rough, brown, and cracked fruit surface.…”
Section: Comparative Transcriptome Analysis Reveals a Multispecies Gementioning
confidence: 99%
“…For PC3, hormone- treated fruit and female reproductive organs had positive scores. In a previous study, each plant tissue also showed convergence in the PCA plot and each PC represented organ-specific gene expression (Fasoli et al 2012). In E. ulmoides, accumulation of TPI is particularly observed in fruit (Nakazawa et al 2009), so PC3 might reflect fruitspecific genes including those related to TPI biosynthesis.…”
mentioning
confidence: 99%
“…In contrast to model plants, progress in identifying the functions of genes in trees is slow because of the limited research approaches and the small number of researchers. Under such circumstances, microarray analysis has been used to analyze the global gene expression pattern in various plant organs, and functionally similar genes and organ-specific genes have been grouped by multivariate analysis, such as principal component analysis (PCA) (Chow et al 2007;Fasoli et al 2012). Based on PCA, unique functional genes in specific organs have been identified (Fasoli et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations